Comparing the effect of bleach and water baths on skin barrier function in atopic dermatitis: a split‐body randomized controlled trial. (7th June 2016) - Shi, V.Y.; Foolad, N.; Ornelas, J.N.; Hassoun, L.A.; Monico, G.; Takeda, N.; Saric, S.; Prakash, N.; Eichenfield, L.F.; Sivamani, R.K.
Abstract : Plain language summary available online